A Case on the Determinants That Drive the Utilization of Mobile Commerce in Malaysia - Gu, Yong Xiang (2013)
Based on the development of wireless communication technology and the popularization of mobile device, mobile commerce becomes the meaningful business all around the world (Barnes 2002). In spite of many studies undertaken, few investigators had explored the driving force of mobile commerce in Malaysia. The aim of this study was to examine the crucial determinants of mobile commerce utilization on the basis of technology acceptance model (TAM) and the theory of reasoned action (TRA). Moreover, this study adopted the quantitative approach and conducted surveys among the public in Malaysia. Data were analyzed by employing factor analysis and multiple regression analysis by means of IBM SPSS software version 20. Service quality (SQ) and social influence (SI) were inquired whether the determinants driving the usage of Malaysian mobile commerce in this study. The findings indicated that perceived usefulness (PU), perceived ease of use (PEOU), cost and social influence (SI) were the fundamental determinants affecting consumers to adopt mobile commerce in Malaysia. In addition, the contributions to research and suggestions for future studies were discussed.